Children’s human rights and diversity in schools: Framing and measuring - Osler, Audrey; Solhaug, Trond (Research in comparative and international education, 2018)
We report on the development of an instrument to measure attitudes to children’s human rights and diversity in schools. It was developed to investigate perceptions of human rights and diversity among students and then teachers in two contrasting areas of Norway. The instrument draws on human rights standards articulated in the United Nations Convention on the Rights of the Child. It is intended for use in future baseline studies, allowing for transnational and comparative analysis of child rights in education. The near-universal ratification of the United Nation Convention on the Rights of the Child provides an agreed international framework for evaluating rights implementation strategies over time. We contextualise the measurement instrument, focusing on rights provision, child protection, and participation in schools. We consider its strengths and possible limitations and discuss the need for a sound human rights conceptual model through which child rights in school settings can be interpreted.